PERSEPSI GURU TERHADAP PELAKSANAAN KURIKULUM MERDEKA - Tatan Zeanl Mutakin; Nurdeni (Jurnal Genta Mulia, 2025)
The Independent Curriculum is a curriculum oriented toward advancements in science and technology, serving as an adaptation to the demands of 21st-century progress. This study aims to explore teachers' perceptions of the implementation of the Independent Curriculum in the education sector. The research employed a survey method by distributing a questionnaire containing 28 statements via Google Forms to teachers from elementary, middle, and high school levels, as well as educational practitioners. A total of 120 teachers participated as respondents. The sampling technique used was saturated sampling, including all collected data as samples. Statistical analysis employed the Rasch model, followed by comparative analysis using SPSS version 20. The findings revealed that, in general, teachers have a positive perception of the Independent Curriculum's implementation. However, teachers also identified shortcomings in its execution, particularly related to the supporting infrastructure and resources.